A facile strategy of constructing composite form-stable phase change materials with superior high thermal conductivity using silicagel industrial wastes. (1st September 2020) - Zhang, Yanwei; Sun, Keyan; Kou, Yan; Wang, Shaoxu; Shi, Quan
Highlights: A high thermal conductivity PCM is synthesized using silicagel wastes. The composite PCM behaves excellent thermal properties in 1000 cycles. The composite PCM exhibits a high thermal conductivity of 5.87 W/(m·K). This work provides a low-cost way of constructing high performace PCM. Abstract: The intrinsic poor thermal transport and liquid leakage of organic phase change materials (PCMs) greatly limit their applications in the field of solar thermal energy conversion and storage. Silica porous materials have usually been employed as supporting matrixes to incorporate PCMs and improve their thermal conductivities. However, the starting materials of synthesizing silica matrixes commonly involve high toxic chemical reagents. In this work, we have developed a facile strategy of constructing composite PCMs based on silicagel industrial wastes, in which paraffin wax (PW), myristic acid (MA) and octadecanol (OD) can be incorporated. Moreover, expanded graphite (EG) has been distributed into the PW composite PCMs to further enhance its thermal conductivity. The obtained composites behave stable form and excellent phase transition properties. The thermal conductivity of the PW composites can be achieved to be 5.87 W/(m·K), nearly 21.7 times higher than that of the pure PW. Furthermore, the 1000 melting-cooling cycle test indicates that the PW composites behave superior thermal cycle stability, exhibiting a promising long-term thermal energy storage application. This synthesis strategy may provide a promising way of low-cost preparation of form-stable composite PCMs with high thermal conductivity for solar thermal energy management and utilization.